The influence of price, service quality, and location on revisit intention through tourist satisfaction as an intervening variable in The Kandi Animal Park Tourism object in Sawahlunto City - Ariani, Echa; Yolanda, Mike (Marketing Management Studies, 2024)
This research aims to analyze the influence of price, service quality and location on revisit intention through tourist satisfaction as an intervening variable at the Kandi Animal Park tourist attraction in Sawahlunto City. This type of research is quantitative with this type of research aiming to find out causes (independent) and effects (dependent) or how variables influence other variables. The population of this study were visitors to the Kandi Animal Park tourist attraction in Sawahlunto City with a sample size of 140 respondents. This research was analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0 Software. The results of this research show that: (1) Price, service quality, location have a significant effect on tourist satisfaction at the Kandi Sawahlunto Animal Park. (2) Price, service quality, location, tourist satisfaction have a significant effect on revisit intention to the Kandi Sawahlunto Animal Park. (3) Price, service quality, location have a significant effect on revisit intention to visit with tourist satisfaction as an intervening variable at the Kandi Sawahlunto Animal Park.